The Advent of the Printing Press and Britain’s Multilingual Textual Culture, 1471–1510 - Jordi Sánchez-Martí (Anglica. An International Journal of English Studies)
This article discusses the effects the new technology of printing had on the rich and multilingual textual culture of late medieval Britain. Before setting up his press in Westminster, William Caxton had books published in Latin, French and English. As soon as he relocated to England, however, he abandoned this multilingual business model and devoted all his energies to print books in English, as did his successors Richard Pynson and Wynkyn de Worde. Not only did they favour English over all other British languages, but promoted a London-based variety of English at the expense of other dialects. Hence, before giving to the press the Scots Contemplacioun of Synnaris by William Touris, Wynkyn de Worde chose to have it Anglicized. When Walter Chepman and Andrew Myllar established a printing press in Edinburgh in 1508, they replicated the choices of their English counterparts, promoting the standard form of Scots and even Scotticizing Middle English texts, such as Sir Eglamour of Artois. I conclude by arguing that the introduction of the printing press in Britain enhanced the prestige of the language variety used by the elite and became instrumental in eroding the balances existing in the British language ecosystem.